Adaptability and stability of corn hybrids in the off season across various agricultural regions in Brazil - Mijone, A. P.; Nogueira, A. P.O.; Hamawaki, O. T.; Maes, M. L.; Pinsetta Junior, J. S. [UNESP] (Genetics and Molecular Research, 2019)
We evaluated how genetic x environment (G x E) interactions affect grain productivity in corn hybrids grown in traditional and non-traditional environments in the off or “second” season. Adaptability and stability of the hybrids was examined by parametric, nonparametric and multivariate methods. In 2016, 24 hybrids were evaluated in seven environments, in 2017, 13 hybrids were evaluated in six environments. The environments were located between the regions of Southwestern and Southeast Goiás state; Triângulo Mineiro and Alto Paranaíba, in the western and northwestern regions of Minas Gerais state. In all trials, complete randomized blocks were adopted, and grain productivity was determined. The statistical analyses were performed with two different softwares: Estabilidade and Genes. It was observed that in both seasons, the locals considered as traditional corn cultivation in the off season Jataí-GO and Montividiu-GO gave the highest yields, with average yields higher than national averages, producing 3859 kg.ha-1 in 2016 and 5562 kg.ha-1 in 2017. The methods of Eberhart and Russell, Lin and Binns modified by Carneiro, Centroid and AMMI gave similar results in the rankings of the adaptation and stability of the hybrids. We concluded that the G x E interaction for grain productivity of corn hybrids grown in the off-season is complex in nature.
Keywords: Adaptation; Interaction G x E; Zea mays